The engaging Romanian teachers in a 3D feedback process - Manea, Natalia; Purcaru, Mihaela (Journal of Economic Development, Environment and People, 2017)
This article presents a comparative overview regarding pupil’s perceptions about quality of the educational act. Some of the key topics that are taken into consideration are the culture of learning environment, the expectations, the confidence and the feelings about the school’s climate. The research is a specific practice within Teach for Romania organization that comes as an innovation method in the Romanian educational system and only applies to teachers of TFR.